Validação da Escala de Avaliação da Percepção Visual (EAPV) com idosos - Silva, Hermesson Daniel Medeiros da (2014)
The aim of this study was to investigate evidence of validity of the Scale for Assessment of Visual Perception (AEFI) with elderly people. He was assisted with the collaboration of 104 people aged over 60 years, of both sexes, selected non-random way and residents in João Pessoa and Campina Grande - PB. Besides the AEFI in data collection, the following instruments were applied: Mini-Mental State Examination (MMSE), Dementia Rating Scale (DRS), Verbal Fluency Test (TVB), the Rey Complex Figure Test (TFCR), the Benton Visual Discrimination Test (TDVB) in Figures Test superimposed Poppelreuter (TFSP), Geriatric Depression Scale (GDS-15), Functional Activities Questionnaire Pfeffer (QAFP), Rating Scale cumulative Illness (CIRS), and a sociodemographic questionnaire. The elderly were interviewed in Centers, Basic Health Units Family - UBSF and three programs from the State University of Paraíba (UEPB) intended for the elderly: Open University in Leisure, Live Aging with Fullness and Open University to Maturity (UAMA). Descriptive analyzes, exploratory factor analysis, parallel analysis, calculation of internal consistency check convergent and discriminant validity and estimation of the parameters of the items using the Item Response Theory (IRT) were performed. Was used in the analyzes SPSS software, version 18.0, 9:20 FACTOR version and language R, version 2.15.1. From the factor analysis, there was an AEFI the factor structure composed of 13 items that assess aspects of figure-ground (2:18), visuocontrução (4, 8, 12, 16 and 20) and visual discrimination (9, 11, 14, 15, 17, and 18). It was possible to certify the convergent and discriminant validity of AEFI from significant correlations with tests that assess visual perception and lack of correlation with those that measure distinct constructs. As the route TRI analysis it was found that the best fit of the data to the model was 1 Rach parameter. We estimated the parameter of difficulty of the items of which varied between -2.81 to 0.93 (M = -0.67, SD = 1.20). It was observed that AEFV provides more information for individuals with visual perception median. Overall, the results indicate that the AEFI was configured as a valid measure for assessing visual perception in the elderly.